PERAN IBU DALAM RUMAH TANGGA DALAM MENINGKATKATKAN PRESTASI ANAK - Yang Gusti Feriyanti; Diana Sari; Nurlida Asni (Yayasan Baitul Hikmah al-Zain, 2025)
The mother's role in the household is not only limited to domestic tasks, but also includes a broader role in educating and guiding children. Mothers have a big influence on children's physical, emotional, social and intellectual development. This research aims to understand how maternal involvement in various aspects of household life can improve children's achievements, both in academic and non-academic fields. Education and Guidance One of the important roles of mothers is in providing education and guidance to children. Mothers who are actively involved in their children's education, such as helping with homework, reading together, and teaching effective study skills, can help children understand subject matter better and improve their academic abilities. In addition, mothers who continue to monitor their children's academic progress and communicate regularly with teachers can also ensure that their children get the necessary support at school.